Micromechanical simulations of the collapse of a submerged granular column - Zarattini Francesco; Pol Antonio; Gabrieli Fabio; Chareyre Bruno (E3S Web of Conferences, 2023)
In this work, we present a numerical study of a granular collapse in a viscous fluid adopting a DEM-PFV (Pore Finite Volume) coupled model. We analyze the time evolution of the collapse and the final morphology of the deposit (triangular or trapezoidal) as a function of the initial solid fraction and column aspect ratio. Finally, we discuss the role of the initial packing fraction of the granular material on the time evolution of the pore pressure. The numerical results are consistent with experimental observation [3] showing the capability of the DEM-PFV coupled model to simulate saturated granular media from triggering to flowing and stopping conditions.